The Logic Behind Crud: Mengelola Alur Manipulasi Data di Laravel - Hanifani , Fildzah Amalina; Salma , Aiva Nabilla; Ningsih , Indri Surya; Elnur , Irsyadi Hanif; Khanafi , Muhammad Almustofa; Mujiastuti , Rully; Sutrisno , Mirza; Risanty , Rita Dewi; Meilina , Popy; Ambo , Sitti Nurbaya; Rosanti , Nurvelly (Dedication : Jurnal Pengabdian Masyarakat, 2026)
The Create, Read, Update, and Delete (CRUD) concept is one of the four basic operations in data management for web applications. However, there are still people, especially students and beginners in the field of information technology, who do not understand the CRUD workflow systematically, making it difficult for them to build web applications that are integrated with databases. This community service activity aims to improve participants' understanding and skills in applying CRUD logic using the PHP programming language and the Laravel framework. The implementation method was carried out through webinars to reinforce theoretical understanding and workshops for hands-on practice. The activity was conducted online and attended by 48 participants from universities. Evaluation was carried out through pre-tests, post- tests, and feedback questionnaires. The results of the activity showed an increase in the average test score of participants from 64 to 85 percent, an average increase of 32.8%. Meanwhile, the satisfaction level results showed that 39.6% agreed and 47.9% strongly agreed. Thus, this activity was able to improve the basic understanding and skills of web application data management.